2014
DOI: 10.1386/ijcm.7.3.397_1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in psychological well-being between choristers and non-choristers in older adults

Abstract: To date, several studies from a variety of fields have demonstrated how musical behaviours such as singing or listening provide multiple benefits on well-being and health. The purpose of the current study was to examine the differences in psychological well-being (PWB) between older adult amateur choristers and non-choristers. The participants comprised 496 men and women who ranged in age between 64 and 78 years. They were distributed into two groups according to whether they participated or not in a choir. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The group is often referred to when talking about perceived benefits of singing (e.g., Judd & Pooley, 2014), and Pearce, Launay and Dunbar (2015) found singing enabled faster social bonding than other creative activities. Group singing fosters a range of social outcomes, including enhanced social support, positive relationships and reduced feelings of isolation and loneliness (Bailey & Davidson, 2002, 2005Clift & Morrison, 2011;Pérez-Aldeguer & Leganés, 2014;Teater & Baldwin, 2012). Participation in group singing can be transformative for individuals and community mobilisation, particularly for marginalised communities (e.g., Dingle, Brander, Ballantyne, & Baker, 2013), which might explain why choral singing is more beneficial than solo singing (Stewart & Lonsdale, 2016;Valentine & Evans, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The group is often referred to when talking about perceived benefits of singing (e.g., Judd & Pooley, 2014), and Pearce, Launay and Dunbar (2015) found singing enabled faster social bonding than other creative activities. Group singing fosters a range of social outcomes, including enhanced social support, positive relationships and reduced feelings of isolation and loneliness (Bailey & Davidson, 2002, 2005Clift & Morrison, 2011;Pérez-Aldeguer & Leganés, 2014;Teater & Baldwin, 2012). Participation in group singing can be transformative for individuals and community mobilisation, particularly for marginalised communities (e.g., Dingle, Brander, Ballantyne, & Baker, 2013), which might explain why choral singing is more beneficial than solo singing (Stewart & Lonsdale, 2016;Valentine & Evans, 2001).…”
mentioning
confidence: 99%
“…The psychological benefits of singing have also been clearly demonstrated. Singing enhances quality of life, satisfaction, emotional well-being, personal growth, and mood (Clift, Hancox, Morrison, Hess, & Kreutz, 2010; Hallam & Creech, 2016; Pérez-Aldeguer & Leganés, 2014), and choir members typically report improvements in physical and mental health (Cohen, Perlstein, Chapline, Kelly, Firth, & Simmens, 2006; Teater & Baldwin, 2012) and psychological well-being (Stewart & Lonsdale, 2016). Singing generates positive emotions like joy and energy, and helps reduce negative emotions like stress (Bailey & Davidson, 2005; Judd & Pooley, 2014).…”
mentioning
confidence: 99%
“…Also, in the qualitative analysis of Pires et al (2017), social benefits were the most reported by 38.4% of the participants of SGP and included categories such as social involvement, socialising and supporting each other. Likewise, in the study of Pérez‐Aldeguer and Leganés (2014), improvements in positive relationships are reported by older adult female choristers ( n = 496). Finally, Petrovsky et al (2020) highlighted two subthemes from interviews with SGP participants: a ‘joyful time together’ and ‘an uplifting experience performing for others’.…”
Section: Discussionmentioning
confidence: 82%
“…The health benefits of engaging in music are well established, both in terms of music therapy (Carr et al 2013, Cole and LoBiondo-Wood 2014, do Amaral et al 2016, Fusar-Poli et al 2018, Martin-Saavedra et al 2018, McConnell et al 2016, Weller and Baker 2011, and in non-therapeutic settings (Clift et al 2010, Dawson 2014, Fancourt et al 2014, Pérez-Aldeguer and Leganés 2014, Román-Caballero et al 2018. Active engagement in music (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Active engagement in music (e.g. playing, singing) impacts psychoneuroimmunological function (Fancourt et al 2014), and has a range of benefits, including those related to cognition (Dawson 2014, Román-Caballero et al 2018, health, and wellbeing (Clift et al 2010, Pérez-Aldeguer andLeganés 2014). Community music may have additional health benefits, owing to the associated social interaction (Tapson et al 2018, White 2016, with musicians reporting benefits regarding their physical and emotional well-being (Barbeau andCossette 2019, Coffman 2009).…”
Section: Introductionmentioning
confidence: 99%